Pengaruh Air Kelapa pada Media Baglog Terhadap Pertumbuhan dan Hasil Jamur Tiram Putih (Pleurotus ostreatus) - Setiyanur, Aris; Santoso, Untung; Mariana, Mariana (Agroekotek View, 2023)
ABSTRACTOne of the potential food crop commodities of horticultural subsectors that continues to increase is white oyster mushrooms.  Utilization of coconut water is one alternative to increase production in the cultivation of oyster mushroom organic nature that is safe for consumers.This study aims to find out the best influence and dose of coconut water administration on baglog media on the growth and yield of white oyster mushrooms. The research was conducted in January-June 2020 in Banjarbaru The experimental method used is Rancagan Acak Lengkap (RAL) one factor in the form of coconut water dose (P). P0 : control, P1 : 8 mL coconut water / baglog, P2 : 12 mL coconut water / baglog, P3 : 15 mL coconut water / baglog and P4: 20 mL coconut water / baglog. Each treatment is repeated 4 times so that there are 20 units of experiments. Each experimental unit has 5 baglogs so there are 100 baglogs of white oyster mushrooms. The results showed a dose of 20 mL coconut water / baglog. is the best treatment for the growth and yield of white oyster mushroom (Pleurotus ostreatus).                                                                                                        Copyright ã 2021 Agroekotek ViewKeywords: Effect of coconut water, white oyster mushrooms.